Universal multifunctional device for heat and mass exchange processes during organic raw material processing - Zagorulko, Aleksey; Zahorulko, Andrii; Kasabova, Kateryna; Chervonyi, Vitalii; Omelchenko, Oleksandr; Sabadash, Sergei; Zahorko, Nadiia; Peniov, Oleg (Eastern-European Journal of Enterprise Technologies, 2018)
The proposed innovative design solution of universal multifunctional device ensures implementation of the maximum number of heat exchange processes. They are: aging, drying, blanching, boiling, boiling soft, infusion, mixing, dissolution and partial extraction. Combination of main heat and mass exchange processes in a single device ensures its technological multioperationality and mobility, due to its location on a mobile platform. On the platform, there are: an engine section; a central support for fixing of the operation technological capacity; a section with a steam generator and a vacuum pump, technical lines. A block with automation tools controls the main operation parameters: speed of rotation of the shaft of the mixer; heating temperature; steam pressure and vacuum pressure is used block with automation. There is also an auxiliary technical retractable lifting rail with a rotating mechanism for unloading and loading of the capacity installed. The structural solution of the multifunctional device ensures a use of replaceable section-modular elements. Heating of the technological capacity occurs due to a flexible radiating resistive electric heater of the radiating type, which ensures that the device reaches the operation mode in 1.5 minutes, an ease of maintenance and reduction of the metal capacity of the structure. We established that the universal multifunctional device provides a reduction in duration of heat exchange processes during its approbation. Namely: aging of organic raw materials by 22 %, blanching ‒ by 25 %, extraction ‒ by 21 %, boiling ‒ by 32 %, drying ‒ by 13 %, infusion ‒ by 43 % and dissolution of the fine dispersed fraction ‒ by 20 %. The cost per unit expended on heating of a unit of product is less by 10 % and 19 % compared to UPTODS-150 and KVM-150 caldron, respectively. This confirms the effectiveness of the accepted innovative solution to ensure mobility, energy and resource efficiency, ease of operation and maintenance of the device